Meningkatkan Peran Orang Tua dalam Pembelajaran Bahasa Inggris Anak Selama Masa Pandemic Covid 19 di Desa Karang Gading Kec. Secanggang - Mutia Hanifa (Maslahah: Jurnal Pengabdian Masyarakat, 2021)
This activity held in Karang Gading Village, Kec. Secanggang, North Sumatra, which attended by 25 peoples. The purpose of this training is to train parents of students in understanding the importance of parenting and their involvement in the children's learning process, especially Learning English and implementing ways that can be done during the pandemic period. The training carried out through lecture, discussion, brainstorming and experience sharing methods during the event. The result showed participants' satisfaction in the training and understand the importance of mentoring in children's English learning during the covid 19 pandemic.